Les Bossats (Ormesson, Paris basin, France): A new early Gravettian bison processing camp. (2nd March 2015) - Lacarrière, Jessica; Bodu, Pierre; Julien, Marie-Anne; Dumarçay, Gaëlle; Goutas, Nejma; Lejay, Mathieu; Peschaux, Caroline; Naton, Henri-Georges; Théry-Parisot, Isabelle; Vasiliu, Ligia
Abstract: In the Paris Basin, the Gravettian techno-complex is documented by a limited number of sites, and radiocarbon dates are available for only three locations: Arcy-sur-Cure (Grande Grotte and Grotte du Renne, Yonne), La Pente-des-Brosses (Montigny-sur-Loing, Seine-et-Marne) and Chamvres (Yonne). This period of human prehistory is poorly known in the region. The recently discovered open-air site of Les Bossats at Ormesson (Seine-et-Marne) includes an early Gravettian occupation with well-preserved faunal remains; this allows for radiocarbon dating and provides information on the ecological context that was previously inaccessible. Located on the southern limit of the maximum extension of loess deposits, Ormesson also provides a well-developed Pleistocene sedimentary sequence. The peculiar geomorphological context of the Gravettian occupation opens new avenues of investigation regarding taphonomy and the possible anthropogenic intra-site spatial organisation. Here we present the primary results of excavations that began in 2009. The strategic location of the site, the richness of the lithic industry, the presence of two well-preserved hearths and associated maintenance features (near which were found both perforated and non-perforated shells), as well as the few elements of bone technology, all suggest that the site was occupied for a relatively long period of time. Flint nodules are primarily obtained from local sources and were used to produce blades and bladelets. The tool kit is, however, dominated by blades likely used in butchering activities, as well as armature and burin production. The occupants of Ormesson seem to have killed and butchered bison near site and imported the most nutritious parts. Portions of reindeer and horse were also imported. The Gravettian occupation at Ormesson thus appears to have been a medium to short-term multi purpose campsite, likely occupied for the time it took to process imported bison carcasses.